Effect of the oral application of a highly selective MMP-13 inhibitor in three different animal models of rheumatoid arthritis. Issue 5 (3rd June 2009) - Jüngel, Astrid; Ospelt, Caroline; Lesch, Mark; Thiel, Melissa; Sunyer, Teresa; Schorr, Olivier; Michel, Beat A; Gay, Renate E; Kolling, Christoph; Flory, Craig; Gay, Steffen; Neidhart, Michel
Abstract : Objective: To evaluate the decrease of cartilage destruction by a novel orally active and specific matrix metalloproteinase 13 (MMP-13) inhibitor in three different animal models of rheumatoid arthritis (RA). Materials and methods: The SCID mouse co-implantation model of RA, the collagen-induced arthritis (CIA) model in mice and the antigen-induced arthritis model (AIA) in rabbits were used. Results: In the SCID mouse co-implantation model, the MMP-13 inhibitor reduced cartilage destruction by 75%. In the CIA model of RA, the MMP-13 inhibitor resulted in a significant and dose-dependent decrease in clinical symptoms as well as of cartilage erosion by 38% (30 mg/kg), 28% (10 mg/kg) and 21% (3 mg/kg). No significant effects were seen in the AIA model. No toxic effects were seen in all three animal models. Conclusion: Although several MMPs in concert with other proteinases have a role in the process of cartilage destruction, there is a need for highly selective MMP inhibitors to reduce severe side effects that occur with non-specific inhibitors. Significant inhibition of MMP-13 reduced cartilage erosions in two of three tested animal models of RA. These results strongly support the development of this class of drugs to reduce or halt joint destruction in patients with RA.